Pengaruh Upah dan Pengalaman Kerja terhadap Produktivitas Karyawan Kerajinan Ukiran Kabupaten Subang - Sulaeman, Ardika (TRIKONOMIKA, 2014)
Background of this research was the low productivity of the employees of wood-carving in Subang district. This study therefore aimed to determine the effect of work experience and wage on employee productivity. The research was conducted on the wood carving business employees through observation of 134 people from 20 wood-carving companies in Subang district. The results of this study indicate that there are positive effects of wage and work experience to work productivity either partially or simultaneously.